Risk management among the poor: The case of microfinancial services - Thankom Arun; Mirko Bendig (Institute for the Study of Labor (IZA), 2010)
This paper argues that the level of financial services provision determines the risk management strategies among the poor. The paper estimates the determinants of the household's use of one, two or all three types of microfinancial services applying ordered probit models and additionally probit models for combinations of them. By doing this on household survey data from Sri Lanka, there is empirical evidence that household's probability to participate in microfinancial services increases with rising self perception towards risk. Further, we find that it depends highly on the type of risk, if a household is more or less likely to use microfinancial services in Sri Lanka, whereas the accessibility to one, two or three microfinancial services is determined by the experience of specific hazards in the past. The study finds that the poor are less likely to use microfinancial services than their better off counterparts.
Keywords: G20; O16; R22; 330; financial markets; financial services; microinsurance; Sri Lanka; South Asia; Armut; Privater Haushalt; Risikomanagement; Mikrofinanz; Versicherung; Sri Lanka